Efficacious and safe control of glycemia using Apidra insulin - Elena Valer'evna Biryukova (Endocrinology Research Centre, 2010)
Diabetes mellitus (DM) is a stably growing pathology leading to micro- and macrovascular complications. Despite high potential of medicamentaltherapy for DM its efficacy needs to be further improved. Uncompensated postprandial hyperglycemia is known to be responsible for many diabeticcomplications. Moreover, it by itself aggravates disturbances of insulin secretion through the toxic effect of glucose. Insulin therapy remains a principaltool for the treatment of DM. Its efficiency was greatly improved with the advent of fast-acting insulin analogs obtained by reducing stability of hexamers.Insulin glulysine (Apidra) is the fastest-acting analog licensed for the treatment of DM1 and DM2 in adult patients in 2004 (FDA, EMEA) andin children above 6 years in 2008 (EMEA). A characteristic feature of this analog is the absence of Zn2+ in its molecule that substitutes polysorbate-20 acting as a surfactant and providing additional protection of monomers from denaturation.